2021
DOI: 10.7759/cureus.17564
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Achilles Repair Using the Mini-Open Approach in Supine Versus Prone Position: A Retrospective Study

Abstract: Surgical repair of the Achilles tendon is a common procedure in cases of acute rupture. Open Achilles tendon surgery with a traditional extensile approach is most often performed in the prone position, but this can lead to numerous complications. The mini-open approach for repair in the supine position may avoid the risks of the prone position. The purpose of this study is to compare perioperative outcomes and differences in cost between patients undergoing acute Achilles rupture repair with mini-open approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 31 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…McKissack et al demonstrated that the overall complication rate of the mini-open supine approach (7.7%) was lower than that of the traditional prone approach (9.3%), while the average cost of the prone approach exceeded that of the supine approach by $1,823 1 . This increased cost, although not significant, may be attributable to longer operating room and post-anesthesia care unit times.…”
Section: Expected Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…McKissack et al demonstrated that the overall complication rate of the mini-open supine approach (7.7%) was lower than that of the traditional prone approach (9.3%), while the average cost of the prone approach exceeded that of the supine approach by $1,823 1 . This increased cost, although not significant, may be attributable to longer operating room and post-anesthesia care unit times.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…The traditional surgical approach is completed with the patient in the prone position with an extensile midline incision. Here we describe a mini-open approach with supine positioning that utilizes a single incision measuring approximately 3 to 4 cm in length and avoids the pitfalls of prone positioning, which include greater operative time and potential difficult airway management, vision loss, and brachial plexus palsies 1 .…”
mentioning
confidence: 99%
See 3 more Smart Citations